Donor support for Health Policy and Systems Research: barriers to financing and opportunities for overcoming them - Alexander Kentikelenis; Abdul Ghaffar; Martin McKee; Livia Dal Zennaro; David Stuckler (BMC, 2022)
Abstract Background The vast investments that have been made in recent decades in new medicines, vaccines, and technologies will only lead to improvements in health if there are appropriate and well-functioning health systems to make use of them. However, despite the growing acceptance by major global donors of the importance of health systems, there is an enthusiasm gap when it comes to disbursing funds needed to understand the intricacies of how, why and when these systems deliver effective interventions. To understand the reasons behind this, we open up the black box of donor decision-making vis-à-vis Health Policy and Systems Research (HPSR) financing: what are the organizational processes behind the support for HPSR, and what are the barriers to increasing engagement? Methods We conducted 27 semi-structured interviews with staff of major global health funders, asking them about four key issues: motivations for HPSR financing; priorities in HPSR financing; barriers for increasing HPSR allocations; and challenges or opportunities for the future. We transcribed the interviews and manually coded responses. Results Our findings point to the growing appreciation that funders have of HPSR, even though it is often still seen as an 'afterthought' to larger programmatic interventions. In identifying barriers to funding HPSR, our informants emphasised the perceived lack of mandate and capacities of their organizations. For most funding organisations, a major barrier was that their leadership often voiced scepticism about HPSR's long time horizons and limited ability to quantify results. Conclusion Meeting contemporary health challenges requires strong and effective health systems. By allocating more resources to HPSR, global donors can improve the quality of their interventions, and also contribute to building up a stock of knowledge that domestic policymakers and other funders can draw on to develop better targeted programmes and policies.